Contamination assessment of a coastal lagoon (Ria de Aveiro, Portugal) using defence and damage biochemical indicators in gill of Liza aurata - An integrated biomarker approach - Oliveira, M. (2009)
Fish gill importance in toxicants uptake, bioconcentration and excretion allied to meagre knowledge on branchial damage/protection responses substantiate this study. Five critical sites in Ria de Aveiro (Portugal) were assessed in comparison with a reference site (Torreira), focusing on Liza aurata gill antioxidant defences versus damage (oxidative and genetic). Only in Barra fish displayed damage (lipid peroxidation) though no differences were found in antioxidants. In all other sites, except Rio, antioxidant alterations were found. Thus, fish from Gafanha, Laranjo and Vagos showed higher total glutathione, glutathione peroxidase and catalase. Higher glutathione reductase and glutathione S-transferase activity was also found in the first and the last sites, respectively. In Laranjo, metallothionein levels were higher though lower in Gafanha and Vagos. In general, damage was not accompanied by defences weakening confirming that predicting damage based on antioxidants depletion is not straightforward. The integrated biomarker response index ranked sites as: Gafanha > Barra > Laranjo > Vagos > Rio > Torreira.